Case Report: Potential Predictive Value of MMR/MSI Status and PD-1 Expression in Immunotherapy for Urothelial Carcinoma - Yu-Ting Ma; Yan Li; Li Yan; Fang Hua; Dong-Guan Wang; Guo-Ying Xu; Hong-Lan Yang; Ying-Jie Xue; Ye-Jun Qin; Dan Sha; Hao Ning; Miao-Qing Zhao; et al. (Frontiers Media S.A., 2022)
Immune checkpoint inhibitors (ICIs) have shown encouraging outcomes against Lynch syndrome (LS)-associated colorectal cancer (CRC) and endometrial cancer with mismatch repair deficient/microsatellite instability-high (dMMR/MSI-H). However, there is as yet no clarity on the safety and efficacy of immunotherapy combined with chemotherapy in LS-associated urothelial carcinoma (UC). Here, we report a patient with recurrent and metastatic LS-associated UC who achieved sustained response to programmed death protein 1 (PD-1) inhibitor combined with chemotherapy over 31 months, during which the side effects of immunotherapy could be controlled and managed. Our findings indicate that the dMMR/MSI status and PD-1 expression in UC may have potential predictive value for the response to PD-1-targeted immunotherapy. Our case supports the inclusion of such combination and/or monotherapy for UC in clinical studies and using dMMR/MSI status and PD-1 expression as potential predictive biomarkers for assessment of the therapeutic response.